The effect of using multichannel twisted tape and nanofluid on the absorber tube's heat transfer and the efficiency of a linear parabolic solar collector - Mustafa, Jawed; Alqaed, Saeed; Sharifpur, Mohsen; Husain, Shahid (Sustainable energy technologies and assessments, 2022)
One of the most important tools for using solar energy is parabolic solar collectors (SCs). To improve the performance of these collectors, creating rotation in the fluid flow by placing twisted tape or helical paths inside the tube is an effective passive method. In this study, the role of three- and four-channel twisted tapes in increasing the rate of heat transfer (RHT) inside the collector adsorbent tube containing water-copper oxide nanofluid and its effect on energy and exergy efficiencies has been investigated numerically. Finite volume method, SIMPLE algorithm and SST k-w turbulence model for solving the equations. The study was conducted for Re = 20000–80000. Numerical results indicated that the highest Nusselt number was related to nanofluids with a volume fraction of 4% in Reynolds number of 80,000, equal to 54.7. Furthermore, the highest coefficient of thermal performance of three-channel twisted tape occurs in Reynolds of 80,000 with a volume fraction of 4%. Moreover, the best efficiency of SCs is related to nanofluid flow with Reynolds of 80,000 and volume fraction of 4%, which is equal to 26%. Furthermore, nanofluid with a volume fraction of 4% has the highest exergy efficiency.